PHARMACOKINETICS OF VIRECHANA KARMA: A SHORT REVIEW - Smita Vinod Zambare (International Journal of Applied Ayurved Research, 2017)
Ayurved is Science of life. Primary aim of Ayurveda is maintain health of healthy person. Now a days panchkarma therapy getting popularity in society. Main reasons of popularity of panchkarma is instant and prolong relief. Virechana is one of the most useful panchkarma theraphy.in opd to ipd all level its give magical result. It is my experience that many cases of kushta and nervous system get dynamic result due to Virechana.so it is important to understand its mechanism. How body act on drug can describe in Pharmacokinetics. Virechana drugs have Ushna, Tikshana, Sukshma, Vyavayi, Vikasi and Adhobhagahar prabhav properties. With own virya & prabhav& property Virechana drugs reach to the heart (hridaya).from hridaya its enter in suksham stratus and liquefied all Dosha (vishyandana) the doshasamghata by virtue of their Ushnaguna and flaccid it.After that its break up (chedana) by their Tikshana and Vikasiguna. The vitiated Pitta-dosha is expelled out through mechanism of VirechanaKarma. In this review article describe all topic related Pharmacokinetics of Virechana karma.